2017
DOI: 10.1186/s12866-017-0946-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbe-host interactions: influence of β-glucans on gene expression of inflammatory cytokines and metabolome profile

Abstract: BackgroundThe aim of this study was to evaluate the effects of β-glucan on the expression of inflammatory mediators and metabolomic profile of oral cells [keratinocytes (OBA-9) and fibroblasts (HGF-1) in a dual-chamber model] infected by Aggregatibacter actinomycetemcomitans. The periodontopathogen was applied and allowed to cross the top layer of cells (OBA-9) to reach the bottom layer of cells (HGF-1) and induce the synthesis of immune factors and cytokines in the host cells. β-glucan (10 μg/mL or 20 μg/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…This suggests that epileptic seizures also induced other metabolic changes.
Figure 5Metabolic networks ( A , B ) and representative physiological systems (C and D) containing the VOCs associated to kindled seizures. Transsulfation 30,32,35 , methionine-homocystaine cycle 38,39,61 , and histidine degradation 42,43 ( A ); fatty acid beta-oxidation networks and glycolysis 28,29,45,46 ( B ); epilepsy and anxiety 49,51,52,54 ( C ); and pheromones 34,50,56 ( D ). Abbreviations: 2-acetyl-pyrroline, 2AP; 5-formiminotetrahydrofolate, 5-formimino-THF; 5-methyltetrahydrofolate, 5-MTHF, aldehyde dehydrogenase 7 family member A1, ALDHTA1; betaine aldehyde dehydrogenase, BADH; cytochrome C oxidase subunit II, COX-2; 3,4-dehydro- exo -brevicomin, DEB; disulfide, dimethyl, DSDM; dimethyl trisulfide, DMTS; formimidoyltransferase cyclodeaminase, FTCD; gamma-aminobutyric acid, GABA; glutamate decarboxylase, GAD; hydrogen sulfide, H 2 S; histidine ammonia-lyase, HAL; phosphatidylcholine, PC; trimethylamine, TMA; 2,3,5-trithiahexane, TTH; vitamin B6, vB6.
…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that epileptic seizures also induced other metabolic changes.
Figure 5Metabolic networks ( A , B ) and representative physiological systems (C and D) containing the VOCs associated to kindled seizures. Transsulfation 30,32,35 , methionine-homocystaine cycle 38,39,61 , and histidine degradation 42,43 ( A ); fatty acid beta-oxidation networks and glycolysis 28,29,45,46 ( B ); epilepsy and anxiety 49,51,52,54 ( C ); and pheromones 34,50,56 ( D ). Abbreviations: 2-acetyl-pyrroline, 2AP; 5-formiminotetrahydrofolate, 5-formimino-THF; 5-methyltetrahydrofolate, 5-MTHF, aldehyde dehydrogenase 7 family member A1, ALDHTA1; betaine aldehyde dehydrogenase, BADH; cytochrome C oxidase subunit II, COX-2; 3,4-dehydro- exo -brevicomin, DEB; disulfide, dimethyl, DSDM; dimethyl trisulfide, DMTS; formimidoyltransferase cyclodeaminase, FTCD; gamma-aminobutyric acid, GABA; glutamate decarboxylase, GAD; hydrogen sulfide, H 2 S; histidine ammonia-lyase, HAL; phosphatidylcholine, PC; trimethylamine, TMA; 2,3,5-trithiahexane, TTH; vitamin B6, vB6.
…”
Section: Discussionmentioning
confidence: 99%
“…Natural products present as potential alternative therapeutic options for several infectious diseases, as antimicrobial agents. [6][7][8][9][10][11][12] Monolaurin (glycerol monolaurate) is a natural compound that is commonly found in coconut oil, 13) which is also considered Generally Recognized as Safe 14) (GRAS) for use in the food industry by the Food and Drug Administration (FDA). 15) Recent studies have shown monolaurin to have broad bioactivity; for example as antibacterial properties.…”
mentioning
confidence: 99%
“…A dual-chamber, oral cell/bacteria co-culture was used to investigate the immunological effects of monolaurin ( Silva et al, 2017 ). HGF-1 cells (1 × 10 5 ) were seed in the basal chamber of a 24-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…DMEM (Lonza, Walkersville, MD, United States) with 10% FBS (Lonza, Walkersville, MD, United States) was used for the medium. The plates were incubated at 37°C in humid air containing 5% CO 2 for 24 h ( Silva et al, 2017 ). Trans Epithelial Electric Resistance (TEER) of each cell layer was measured with a Millicell-ERS Volt-Ohm Meter (Millipore, Bedford, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation